2016
DOI: 10.1093/nar/gkw128
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative motion of a key positively charged residue and metal ions for DNA replication catalyzed by human DNA Polymerase-η

Abstract: Trans-lesion synthesis polymerases, like DNA Polymerase-η (Pol-η), are essential for cell survival. Pol-η bypasses ultraviolet-induced DNA damages via a two-metal-ion mechanism that assures DNA strand elongation, with formation of the leaving group pyrophosphate (PPi). Recent structural and kinetics studies have shown that Pol-η function depends on the highly flexible and conserved Arg61 and, intriguingly, on a transient third ion resolved at the catalytic site, as lately observed in other nucleic acid-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(104 citation statements)
references
References 76 publications
13
91
0
Order By: Relevance
“…72 Recent computational investigations provided a rational for this conformational change, suggesting that in the "down" conformation, Arg61 stabilizes the formation of a catalytic complex for the polymerase reaction. 73 Remarkably, MD simulations of the activated pol−η show that Arg61 mainly adopts a "down" conformational state, rarely transitioning in the "up" conformational state, similar to what observed in the present study for CRISPR−Cas9 (Figures 3 and 5A, left panel). In CRISPR−Cas9, DNA cleavage assays by capillary electrophoresis have shown that the R976A mutation reduces the cleavage of the NTS.…”
Section: Journal Of Chemical Information and Modelingsupporting
confidence: 88%
See 1 more Smart Citation
“…72 Recent computational investigations provided a rational for this conformational change, suggesting that in the "down" conformation, Arg61 stabilizes the formation of a catalytic complex for the polymerase reaction. 73 Remarkably, MD simulations of the activated pol−η show that Arg61 mainly adopts a "down" conformational state, rarely transitioning in the "up" conformational state, similar to what observed in the present study for CRISPR−Cas9 (Figures 3 and 5A, left panel). In CRISPR−Cas9, DNA cleavage assays by capillary electrophoresis have shown that the R976A mutation reduces the cleavage of the NTS.…”
Section: Journal Of Chemical Information and Modelingsupporting
confidence: 88%
“…13 The use of a recently developed accelerated MD methodology i.e., a Gaussian accelerated MD (GaMD)further enabled broad exploration of the conformational dynamics of the RuvC domain over longer time scales. As a result, an arginine finger is found to stably contact the scissile phosphate, as also observed in other Mg 2+ -aided phosphatases 70 and DNA/RNA two-metal aided enzymes, 55,[71][72][73]83 with the function of stabilizing the formation of a catalytically active complex. Overall, the agreement with the available experimental studies on CRISPR−Cas9 and the analogies found with other two-metal aided enzymes support the model proposed in the present study, offering a reliable description of the active site chemistry.…”
Section: ■ Conclusionsupporting
confidence: 63%
“…Based on molecular dynamics (MD) simulations, a "hopping" model for PP i release was proposed, where a few positively charged residues along the exit channel form the hopping sites and facilitate the process of PP i release (18). Another MD simulation study of a Y-family DNA polymerase (human Pol ) suggested that a highly flexible and conserved arginine residue (Arg-61) acts concertedly with a third transient metal ion that forms an "exit shuttle" for the leaving PP i group (19). The actual PP i release should be a fast process if the channel connecting the internal active site to the external solvent is large enough for a PP i molecule to freely diffuse (49).…”
Section: Tablementioning
confidence: 99%
“…Because the translocation step is kinetically "invisible" in rate measurements, a direct measurement of translocation by a polymerase has been sadly lacking until Malinen et al (17) monitored RNA polymerase (RNAP) translocation along its DNA substrate using fluorescent base analogs and revealed fast translocation rates after incorporation of various nucleotides, with half-lives (t1 ⁄ 2 ) between 7 and 12 ms. Although atomic level details of PP i release by polymerases are still elusive (18,19), it is generally thought to be fast (1,2) with only few exceptions after mismatched or modified nucleotides are incorporated (20 -22). Our recent measurements of the rates of polymerization and pyrophosphate release by HIVRT in single turnover experiments with DNA templates showed that pyrophosphate (PP i ) dissociation was fast after nucleotide incorporation so that it did not contribute to enzyme specificity (k cat /K m ).…”
mentioning
confidence: 99%
“…Further parallels can also be made between the PfA-M17 system and the diverse enzymes that operate via the conserved two-metal ion mechanism (with associated basic residue). A particularly striking similarity is observed between the human DNA Polymerase-η (Pol-η) and PfA-M17; Pol-η operates via a highly dynamic and cooperative process that involves transient recruitment of a third metal ion (60). The conserved basic residue of Pol-η, Arg61, is highly flexible, and specific conformations of Arg61 (sampled as part of a large equilibrium ensemble) serve to recruit incoming substrate, facilitate the reaction, and act as an exit shuttle (60).…”
Section: Discussionmentioning
confidence: 99%